Injectable artificial bone repair material and preparation method thereof
By combining the mixed powder of calcium sulfate coarse powder and fine powder with the curing liquid, a high-strength injectable artificial bone repair material is formed, which solves the problem of biocompatibility and mechanical strength mismatch of existing bone repair materials, and realizes the High compressive strength and good osteoinduction effect.
Patent Information
- Application Number
- CN202411150765.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-20
AI Technical Summary
Existing bone repair materials, such as bioglass, calcium phosphate and calcium sulfate, have problems with mismatch in biocompatibility, mechanical strength and degradation speed, resulting in poor results in bone defect repair.
Use a mixed powder of calcium sulfate coarse powder and fine powder to mix particle size and morphology, combine with the curing liquid to form an injectable slurry, ensuring high strength and good injectability, reducing microscopic defects and pores after curing, and improving resistance. Pressure strength.
It achieves uniform mixing with the curing liquid at extremely low liquid-solid ratio, with good injectability and high compressive strength, reducing the risk of secondary collapse during compression after repair of bone defects, and enhancing osteoinduction and anti-inflammatory characteristic.
Smart Images

Figure CN119158072A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of material processing, and in particular to an injectable artificial bone repair material and a preparation method thereof. Background Art
[0002] Due to some trauma, infection, tumor and other factors, the bone loses some bone mass, forming a bone defect. Due to the large defect gap, most bone defects are difficult to heal on their own, and finally form a nonunion. The main methods used to treat bone defects include traditional autologous bone transplantation, allogeneic bone, xenogeneic bone transplantation, and artificial synthetic bone transplantation.
[0003] Autologous bone is still the best material for repairing bone defects. However, its application in clinical practice is limited due to the limited amount of bone available and potential infection opportunities. Although allogeneic bone and xenogeneic bone transplantation have the function of conducting osteogenesis, they also have many shortcomings, such as antigenicity and the possibility of transmitting pathogens, limited sources and some social and ethical reasons, so they cannot be ideal bone transplantation materials. In order to overcome the defects of the above materials, people began to study artificial bone repair materials, using materials science and biomedical technology to produce artificial bones with strength and performance close to natural human bones.
[0004] Among the various bone repair materials currently available in clinical practice, there are mainly bioglass, calcium phosphate (HA and TCP, etc.), polymethyl methacrylate (PMMA) bone cement, calcium sulfate, etc. Among them, bioglass has strong activity and superior bone formation ability, but its strong alkalinity leads to certain hidden dangers in biocompatibility; PMMA bone cement has high mechanical strength after curing, but its heat release during solidification and non-degradability prove that it is not the most ideal bone repair material; calcium phosphate artificial bone has good biocompatibility and degradability, but its mechanical strength after curing is not high (compressive strength 30-60MPa), and the degradation time is usually more than one year, which does not match the growth rate of new bone. In the later stage of degradation, new bone cannot be generated due to space occupation; calcium sulfate materials have been used in the field of clinical bone filling for more than 100 years. A large number of basic research and clinical applications have confirmed that calcium sulfate has good biocompatibility and excellent bone conduction, so that its degradation in the body is accompanied by the creeping growth of osteoblasts inside the calcium sulfate to achieve the purpose of bone repair. It is a bone transplant substitute with great clinical application potential.
[0005] In the 1990s, Wright Medical Technology Co., Ltd. in the United States developed and produced a new generation of bone transplant substitute product OsteoSet with calcium sulfate as the matrix. It is calcium sulfate hemihydrate (CaS04·1 / 2H20) made using a special method. It has good biocompatibility and bone conduction, and has been approved by the US FDA for clinical use. Subsequently, Wright launched a new generation of MIIG injectable artificial bone kits with better performance. In clinical applications, calcium sulfate powder and curing liquid are mixed and injected into the patient's body, which has stronger plasticity and fills the bone cavity more fully.
[0006] A large amount of basic research has found that high-strength calcium sulfate hemihydrate artificial bone mainly relies on the microscopic specific crystal form of α-calcium sulfate hemihydrate, that is, it has a hexagonal short columnar microstructure. At present, there are three common methods for preparing calcium sulfate hemihydrate powder: autoclave method, pressurized hydrothermal method and normal pressure salt solution method.
[0007] The calcium sulfate hemihydrate powder prepared by the atmospheric pressure salt solution method usually has a low crystallinity, resulting in a low compressive strength after solidification. Chinese Patent CN 102633287 discloses a method for synthesizing medical calcium sulfate hemihydrate by the atmospheric pressure salt solution method with ethanol added to the reaction system. The method obtains a relatively uniform hexagonal short columnar crystal form, but there are still bulges in the C-axis direction, and the strength after solidification is less than 40MPa; the autoclave method is to recrystallize calcium sulfate dihydrate into α-calcium sulfate hemihydrate by steam in a closed pressure vessel. The method is characterized by high energy consumption, large fluctuations in product quality, and difficulty in ensuring the crystal form and phase of the product. Chinese Patent CN1 12390555 discloses a method for preparing calcium sulfate hemihydrate by autoclaving, but it does not disclose the microscopic crystal form of the prepared calcium sulfate hemihydrate, and the compressive strength after solidification is only about 60MPa; the hydrothermal method is known for its uniform reaction and stable products. The calcium sulfate hemihydrate prepared by this method has high crystal phase purity and good crystal stability. Chinese patent CN103723757 discloses a calcium sulfate hemihydrate powder synthesized by a hydrothermal method, but its compressive strength after solidification is only 40-50MPa. Summary of the invention
[0008] In order to solve the above technical problems, the present application discloses an injectable artificial bone repair material, comprising a mixed powder of coarse calcium sulfate powder and fine calcium sulfate powder, wherein the particle size of the coarse calcium sulfate powder is 20 to 100 μm, and the particle size of the fine calcium sulfate powder is less than or equal to 7 μm. 。
[0009] Preferably, the mass ratio of the coarse calcium sulfate powder to the fine calcium sulfate powder is 1:0.25 to 1:2.
[0010] Preferably, the injectable artificial bone repair material meets at least one of the following characteristics:
[0011] The microscopic morphology of the coarse powder is at least partially columnar;
[0012] The microscopic morphology of the calcium sulfate fine powder is irregular.
[0013] Preferably, the columnar morphology is at least partially a hexagonal columnar morphology.
[0014] Preferably, the material of the calcium sulfate coarse powder is α-calcium sulfate hemihydrate, and the material of the calcium sulfate fine powder is any one of α-calcium sulfate hemihydrate or β-calcium sulfate hemihydrate or a combination of the two.
[0015] Preferably, the XRD diffraction pattern of the calcium sulfate coarse powder matches the material card number 41-0224.
[0016] Preferably, the injectable artificial bone repair material further comprises a solidifying liquid, and the solidifying liquid is mixed with the mixed powder to form an injectable slurry. The mixed powder absorbs the solidifying liquid and solidifies to form an artificial bone.
[0017] The main component or all components of the solidifying liquid of an injectable artificial bone repair material are water.
[0018] Preferably, the liquid-to-solid ratio of the volume of the solidifying liquid to the mass of the mixed powder is 0.23:1 to 0.3:1.
[0019] Preferably, the initial setting time of the injectable slurry is 2 to 9 minutes, and the final setting time of the injectable slurry is 4 to 13 minutes.
[0020] Preferably, one or more of a retarder, an active factor and an antibiotic may be added to the solidifying liquid.
[0021] A method for preparing an injectable artificial bone repair material, characterized in that it comprises the following steps:
[0022] S1: providing calcium sulfate powder;
[0023] S2: obtaining calcium sulfate fine powder by grinding calcium sulfate coarse powder;
[0024] The particle size of the calcium sulfate coarse powder is 20 to 100 μm, and the particle size of the calcium sulfate fine powder is less than or equal to 7 μm;
[0025] The coarse powder and the fine powder are mixed to obtain the mixed powder of the injectable artificial bone repair material.
[0026] Preferably, the preparation method of calcium sulfate is a normal pressure salt solution reaction method, an autoclave method or a hydrothermal reaction method.
[0027] Preferably, the calcium sulfate powder is α-calcium sulfate hemihydrate powder.
[0028] Preferably, the mass ratio of the coarse powder to the fine powder is in the range of 1:0.25 to 1:2.
[0029] Implementing the embodiments of the present application has the following beneficial effects:
[0030] The present application can be evenly mixed with the solidifying liquid at an extremely low liquid-to-solid ratio and has good injectability by adjusting the morphology, size and / or mass ratio of the coarse calcium sulfate powder and the fine calcium sulfate powder in the mixed powder.
[0031] The XRD diffraction pattern of the calcium sulfate coarse powder matches the material card number #41-0224, which is an α-hemihydrate calcium sulfate crystal form. Each particle in the microscopic morphology has edges, and at least part of it is in a hexagonal columnar morphology, with a good lattice structure. Part of it is ground and crushed to obtain calcium sulfate fine powder, and the coarse powder and fine powder are distributed by particle size, and mixed to obtain a high-strength injectable calcium sulfate artificial bone repair material. The repair material is mixed with the solidifying liquid and injected into the bone defect. The mixing of coarse powder and fine powder can effectively reduce the microscopic defects of the injectable slurry after solidification. After solidification, there are fewer microscopic pores and a denser structure. After solidification, it has a very high compressive strength, which reduces the risk of secondary collapse when the bone defect is compressed after repair.
[0032] In addition, the coagulation time of injectable artificial bone can be controlled and regulated by certain organic additives to further increase the osteoinductive properties and anti-inflammatory properties of the artificial bone. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the preparation method and application of an injectable artificial bone repair material described in the present application, the drawings required for the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0034] Figure 1-4 The powder scanning electron microscope image provided in the embodiment of the present application;
[0035] Figure 5 The powder XRD pattern provided in the examples of the present application;
[0036] Figure 6 Diagram of injectable slurry injection extrusion provided in the embodiment of the present application;
[0037] Figure 7 The injectable slurry is filled into the mold to prepare a φ4*6~4*8mm cylinder. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0039] As used herein, "one embodiment" or "embodiment" refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present application. The content of the present invention may be more easily understood by referring to the following detailed description of the preferred implementation method of the present invention and the included embodiments. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by a person of ordinary skill in the art to which the present invention belongs. In the event of a conflict, the definitions in this specification shall prevail.
[0040] For the purpose of the following detailed description, it should be understood that the present invention may adopt various alternative changes and step sequences, unless expressly specified to the contrary. In addition, except in any operating examples, or otherwise indicated, all numbers representing the amount of ingredients used in the specification and claims should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters set forth in the following specification and the attached claims are approximate values that vary according to the desired performance to be obtained by the present invention. At least it is not intended to limit the application of the doctrine of equivalents to the scope of the claims, and each numerical parameter should at least be interpreted according to the number of reported significant figures and by applying ordinary rounding techniques.
[0041] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements.
[0042] When a numerical range is disclosed herein, the above range is deemed to be continuous and includes the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all sub-ranges included therein. For example, a specified range from "1 to 10" should be deemed to include any and all sub-ranges between a minimum of 1 and a maximum of 10. Exemplary sub-ranges of ranges 1 to 10 include, but are not limited to, 1 to 6.1, 3.5 to 7.8, 5.5 to 10, etc.
[0043] Before further describing the embodiments of the present application in detail, the nouns and terms involved in the embodiments of the present application are explained. The nouns and terms involved in the embodiments of the present application are subject to the following interpretations.
[0044] Injectability: refers to the percentage of the total mass of the slurry that can be injected through a syringe after the powder is mixed into a slurry at a certain liquid-solid ratio.
[0045] Initial setting time, final setting time: refer to standards - YY 0271.1 and GB / T 1346, mix the curing liquid and powder into an injectable slurry at a liquid-to-solid ratio of 0.23mL / g, fill it into a special stainless steel mold with a diameter of 15mm and a height of 5mm, and quickly put it into a curing box at 37±1℃ and a humidity of ≥95%. Use a Vicat instrument to test 5min after mixing. When the Vicat instrument needle cannot completely penetrate the paste, it can be marked as initial setting, and the time required is recorded as the initial setting time. When the Vicat instrument needle cannot leave an imprint on the surface of the paste, it is marked as final setting, and the time required is recorded as the final setting time.
[0046] The present application discloses an injectable artificial bone repair material, comprising a mixed powder of calcium sulfate coarse powder and calcium sulfate fine powder, wherein the particle size of the calcium sulfate coarse powder is 20 to 100 μm, and the particle size of the calcium sulfate fine powder is less than or equal to 7 μm. The particle size range of the coarse powder defined in the present invention is obtained by screening, specifically using a sieve in the range of 20 μm to 100 μm for screening. For example, in order to obtain a particle size range of 30 to 50 um, a sieve of 50 μm and 30 μm is selected for two screenings. The calcium sulfate coarse powder and the calcium sulfate fine powder are mixed in a mass ratio of 1:0.25 to 1:2, and then mixed with a solidifying liquid to form an injectable slurry.
[0047] In some embodiments, the calcium sulfate coarse powder is made of α-hemihydrate calcium sulfate, which, under a scanning electron microscope, at least partially presents a columnar morphology, wherein the columnar morphology mainly presents a hexagonal short columnar morphology and a hexagonal short columnar morphology, and its XRD diffraction pattern matches the material card number #41-0224, reference Figure 5 shown.
[0048] Specifically, the particle size of the calcium sulfate coarse powder can be 50-100 μm, and the particle size of the calcium sulfate fine powder can be less than 7 μm. The mass ratio of the calcium sulfate coarse powder to the calcium sulfate fine powder can be 1:0.25, 1:0.6, 1:0.7, 1:1, 1:1.2, 1:1.3, 1:1.5 or 1:2.
[0049] Calcium sulfate coarse powder is obtained by screening, and the powder with smaller or larger particle size after screening can be subjected to different ball milling processes to obtain calcium sulfate fine powder in the range of 1 to 7 μm. When the fine powder is in the range of 5 to 7 μm, when the mixed powder obtained by mixing with the coarse powder in a ratio of 1:1 is mixed with solid and liquid, the coagulation time and injectability of the formed injectable slurry are the most balanced, and the compressive strength of the artificial bone obtained after solidification is high; when the fine powder is in the range of 1 to 5 μm, the smaller the particle size of the fine powder in the mixed powder, the faster the coagulation time, the injectability is not affected, but the injectability time is shortened, and the compressive strength is slightly improved; when the particle size is less than 1 μm, the coagulation time of the mixed powder will be further shortened, and the existing technical means will not be able to inject in time, which is not conducive to clinical operation; when the particle size is greater than 7 μm, no matter how it is mixed with the coarse powder of 30 to 100 μm, the injectability of the finished product is poor, the amount of water required for standard consistency mixing is greater, and the coagulation strength is also lower.
[0050] The material of the calcium sulfate fine powder can be any one of α-calcium sulfate hemihydrate or β-calcium sulfate hemihydrate or a combination of the two.
[0051] The screening method of calcium sulfate coarse powder and calcium sulfate fine powder is as follows:
[0052] The α-calcium sulfate hemihydrate powder is sieved using a 100 μm aperture sieve to obtain calcium sulfate powder with a particle size of less than or equal to 100 μm; a 20-50 μm aperture sieve is selected for sieving, specifically, a 20, 30, or 50 μm aperture sieve can be selected, and finally a calcium sulfate coarse powder with a coarser particle size of 20-100 μm, 30-100 μm, or 50-100 μm is obtained.
[0053] The sieved powder is further ground, specifically, by ball milling, the ball mill speed is 300-600rpm, the ball milling time is 20-120min, and the calcium sulfate fine powder with a particle size of less than or equal to 7μm is obtained. By controlling the ball mill speed and the ball milling time, a finer calcium sulfate fine powder size can be obtained. Preferably, the calcium sulfate fine powder can be a powder with a particle size of less than or equal to 7, 6, 5, 4, 3, 2 or 1μm, specifically, the particle size range of the calcium sulfate fine powder is 3-7μm, 3-5, 2-7, 2-5, 1-7 or 1-5μm.
[0054] In some embodiments, residual powder with a particle size of less than 20-50 μm is selected and ball-milled at 500 rpm for 60 min to obtain calcium sulfate fine powder with a particle size of 500 nm to 7 μm, and calcium sulfate fine powder with a particle size of less than or equal to 7 μm can be obtained.
[0055] In actual use, the specific grinding method is not limited, and the sieved powder can be ground by other methods. The type of calcium sulfate fine powder is also not limited. α-calcium sulfate hemihydrate powder of any particle size can be used for grinding and crushing to obtain calcium sulfate fine powder with a particle size of less than or equal to 7 μm. α-calcium sulfate hemihydrate powder, β-calcium sulfate hemihydrate powder, or a mixture thereof can also be used for grinding and crushing to obtain calcium sulfate fine powder with a particle size of less than or equal to 7 μm.
[0056] Wherein, the hydrothermal preparation method of α-calcium sulfate hemihydrate powder is as follows:
[0057] S1: providing a crystal conversion agent solution and calcium sulfate dihydrate powder;
[0058] S2: mixing the crystal conversion agent solution and calcium sulfate dihydrate powder to obtain calcium sulfate slurry;
[0059] S3: pouring the calcium sulfate slurry into a reactor for hydrothermal reaction to obtain a primary product;
[0060] S4: filtering and dehydrating the primary product, and drying it to obtain the calcium sulfate coarse powder.
[0061] The crystal-changing agent is a combination of an organic acid salt and an inorganic salt, specifically, the organic acid salt is one or more of sodium citrate and sodium succinate, and the inorganic salt is one or more of aluminum sulfate, sodium sulfate and magnesium sulfate. The crystal-changing agent and purified water are mixed in a certain proportion to obtain a crystal-changing agent solution.
[0062] Through the synergistic effect of organic and inorganic crystal inversion agents, the dehydration and recrystallization process of calcium sulfate dihydrate under high temperature and high pressure is affected, and the growth of the c-axis of calcium sulfate hemihydrate grains during the crystallization process is inhibited. The α-calcium sulfate hemihydrate powder obtained after the hydrothermal reaction has a microscopic morphology reference Figure 1 As shown in the figure, under the scanning electron microscope, each particle has edges, and the main particles are columnar in shape. Among the columnar morphologies, they are mainly hexagonal short columnar and hexagonal short columnar. Its XRD diffraction pattern matches the material card number #41-0224, reference Figure 5 shown.
[0063] In some embodiments, the α-calcium sulfate hemihydrate powder can also be prepared by a normal pressure salt solution reaction method or an autoclave method.
[0064] The injectable artificial bone repair material of the present application is formed by re-coordinating the particle size of α-calcium sulfate hemihydrate powder to form a mixed powder, which can be evenly mixed with a solidifying liquid at an extremely low liquid-to-solid ratio and has good injectability. Figure 6 As shown, the liquid-to-solid ratio of the solidifying liquid (mL) to the mixed powder (g) is 0.23:1 to 0.3:1.
[0065] Specifically, the liquid-to-solid ratio of the solidifying liquid to the mixed powder may be 0.23:1, 0.24:1 or 0.25:1.
[0066] After the mixed powder and the solidifying liquid are mixed in the above proportion, an injectable slurry is formed, which is injected into the bone defect site. After solidification, it has a high compressive strength, reducing the risk of secondary collapse of the bone defect site when it is compressed after repair.
[0067] The solidifying liquid generally selects a separate sterile water for injection, and a retarder can also be added to the sterile water for injection according to functional considerations. Specifically, the retarder includes one or more of polyacrylic acid, xanthan gum, sodium polyaspartate, malic acid, and betaine.
[0068] Since calcium sulfate materials have excellent bone conduction properties but poor bone induction properties, the bone-promoting effect of the material can be improved by adding active factors to the powder or solidifying liquid of the artificial bone repair material. The active factors can be bone morphogenetic protein BMP-2, etc.
[0069] For bone repair treatments in areas prone to clinical infection, or where lesion areas are difficult to scrape clean, and where anti-inflammatory requirements are required for bone repair materials, antibiotics and other drugs can be added to the injectable slurry that has been mixed with the solidifying liquid during clinical use of the product, thereby reducing the probability of inflammation in the bone repair area.
[0070] In some embodiments, the injectable slurry mixed at different liquid-solid ratios is filled into a mold to prepare a φ4*6~4*8mm cylindrical artificial bone, as shown in Table 1, and is cured in a constant temperature and humidity curing box at 37°C and tested for its initial setting time and final setting time. After curing for 24 hours, a strength test is performed to determine the compressive strength.
[0071] The following is an introduction to the preparation of an injectable artificial bone repair material of the present application based on specific examples.
[0072] Example 1
[0073] Weigh purified water and place it in the lining of a reactor with magnetic stirring, add crystal conversion agents sodium citrate and anhydrous magnesium sulfate, stir thoroughly until completely dissolved, then add calcium sulfate dihydrate, stir into a uniform calcium sulfate slurry, close the reactor, and start heating reaction. After the reaction is completed, first evacuate the excess steam in the reactor, then quickly open the reactor cover, take out the lining, and quickly pour the primary product in the lining into a suction filtration tank. After draining excess water, add anhydrous ethanol to the suction filtration tank, filter again, and after the filtration is completed, completely dry the material in a drying oven to finally obtain α-calcium sulfate hemihydrate powder, whose microscopic morphology is as follows Figure 1 As shown, the synthesized powder phase is consistent with the characteristic peaks of calcium sulfate hemihydrate of standard material card #41-0224 ( Figure 5 ).
[0074] Sterile water for injection was selected as the solidifying liquid, and the hydrothermally synthesized α-hemihydrate calcium sulfate powder was mixed with the solidifying liquid at different liquid-solid ratios to test its injectability (the percentage of the injected mass to the blended mass), setting time and compressive strength. The results are shown in Table 1. It can be seen that the hemihydrate calcium sulfate powder that has not undergone particle size distribution, after being mixed with the solidifying liquid, has a poor injectable slurry, a long initial setting time, and a weak compressive strength of the formed artificial bone.
[0075] Example 2
[0076] The hydrothermally synthesized α-hemihydrate calcium sulfate powder of Example 1 was sieved using 100 μm and 30 μm sieves to obtain calcium sulfate coarse powder with a particle size range of 30-100 μm. The powder of the part less than 30 μm was further ball-milled at a ball milling parameter of 500 rpm and a ball milling time of 30 min to obtain calcium sulfate fine powder. The calcium sulfate coarse powder and the calcium sulfate fine powder were uniformly mixed at a mass ratio of 1:1.5 to form a mixed powder. The microscopic morphology of the mixed powder was referenced to Figure 2 As shown, the mixed powder is mixed with sterile water for injection at different liquid-solid ratios. When the mixed powder is mixed with sterile water for injection at a liquid-solid ratio of 0.23, it is prepared into a uniform injectable slurry, which is then transferred to a syringe with a spoon. The syringe is slowly pushed to inject the calcium sulfate artificial bone into the watch glass and the beaker containing physiological saline. Figure 4 As shown, it was observed that the artificial bones after injection maintained a good shape and did not disintegrate even if immediately injected into the liquid. The artificial bones after injection solidified after 2-5 minutes.
[0077] The injectability, setting time, compressive strength and other properties after mixing are shown in Table 1; it can be seen that after the hemihydrated calcium sulfate powder has been redistributed in particle size and mixed with the solidifying liquid, when the liquid-solid ratio is 0.23, the injectable slurry formed has an injectability of 92%, a short initial setting time, and the compressive strength of the artificial bone formed can reach 92MPa. When the liquid-solid ratio is 0.25, the injectable slurry formed has an injectability of 96%. Although it does not affect the setting time, the compressive strength of the artificial bone formed is not as good as the artificial bone formed with a liquid-solid ratio of 0.23. This shows that the mixed powder of the present application can form artificial bones with strong compressive strength under lower liquid-solid ratio conditions.
[0078] Example 3
[0079] The hydrothermally synthesized α-hemihydrate calcium sulfate powder of Example 1 was sieved using 100 μm and 30 μm sieves to obtain coarse calcium sulfate powder with a particle size range of 30-100 μm. The powder with a particle size less than 30 μm was further ball-milled at a ball milling parameter of 500 rpm for 1 h to obtain fine calcium sulfate powder. The coarse calcium sulfate powder and the fine calcium sulfate powder were uniformly mixed at a mass ratio of 1:0.25. The microscopic morphology of the mixed powder was referenced to Figure 3 As shown, the mixed powder is mixed with purified water at different liquid-solid ratios, and the injectability, setting time, compressive strength and other properties of the mixed powder are shown in Table 1. It can be seen that the semi-hydrated calcium sulfate powder after the particle size distribution is redistributed, after being mixed with the solidifying liquid, when the liquid-solid ratio is 0.3, the injectable slurry formed can be injected up to 92%, the initial setting time is short, and the compressive strength of the formed artificial bone can reach 85MPa. Compared with Example 2, the reduction of fine powder not only affects the liquid-solid ratio and setting time, but also plays a role in supplementing the gap of coarse powder during solidification, further enhancing the compressive strength of artificial bone.
[0080] Example 4
[0081] The α-calcium sulfate hemihydrate powder hydrothermally synthesized in Example 1 was sieved using 100 μm and 30 μm sieves to obtain calcium sulfate coarse powder with a particle size range of 30-100 μm. The powder <30 μm was further ball-milled at a ball milling parameter of 500 rpm for 2 h to obtain calcium sulfate fine powder. The calcium sulfate coarse powder and the calcium sulfate fine powder were uniformly mixed at a mass ratio of 1:1. The microscopic morphology of the mixed powder was referenced to Figure 4 As shown, the mixed powder is mixed with purified water according to different liquid-solid ratios, and the injectability, setting time, compressive strength and other properties after mixing are shown in Table 1. It can be seen that the semi-hydrated calcium sulfate powder after the particle size distribution is redistributed, after mixing with the solidifying liquid, when the liquid-solid ratio is 0.25, the injectable slurry formed can be injected up to 91%, the initial setting time is short, and the compressive strength of the formed artificial bone can reach 90MPa. Compared with Examples 2 and 3, it is further explained that under the same liquid-solid ratio, for the distribution of the particle size of the coarse powder and the fine powder in the mixed powder, under the condition of the same liquid-solid ratio, the injectable slurry plays the role of adhesion and filling the coarse powder during the solidification process, which can effectively reduce the microscopic defects after the injectable slurry is solidified, and the microscopic pores are less after solidification, the structure is more compact, and the strength is higher. After the injectable slurry is solidified to form an artificial bone, the fine powder can also serve to transmit and disperse the load of the coarse powder. Although the coarse powder has a larger particle size and requires more solidifying liquid, its short columnar structure has a certain lattice strength, which can better withstand pressure, improve the stability of artificial bone, and reduce the risk of secondary collapse when the bone defect is under pressure after repair.
[0082] Table 1
[0083]
[0084]
[0085] The above disclosure is only the preferred embodiment of the present application, which certainly cannot be used to limit the scope of rights of the present application. Therefore, equivalent changes made according to the claims of the present application are still within the scope covered by the present application.
Claims
1. An injectable artificial bone repair material, characterized in that: The injectable artificial bone repair material comprises a mixed powder of calcium sulfate coarse powder and calcium sulfate fine powder, wherein the particle size of the calcium sulfate coarse powder is 20 to 100 μm, and the particle size of the calcium sulfate fine powder is less than or equal to 7 μm. 。 2. The injectable artificial bone repair material according to claim 1, characterized in that: The mass ratio of the coarse calcium sulfate powder to the fine calcium sulfate powder is 1:0.25 to 1:
2.
3. The injectable artificial bone repair material according to claim 1, characterized in that: The microscopic morphology of the coarse powder is at least partially columnar.
4. The injectable artificial bone repair material according to claim 3, characterized in that: The columnar morphology is at least partially a hexagonal columnar morphology.
5. The injectable artificial bone repair material according to claim 1, characterized in that: The material of the calcium sulfate coarse powder is α-calcium sulfate hemihydrate, and the material of the calcium sulfate fine powder is any one of α-calcium sulfate hemihydrate and β-calcium sulfate hemihydrate or a combination of the two.
6. The injectable artificial bone repair material according to claim 1, characterized in that: The injectable artificial bone repair material also includes a solidifying liquid. After the solidifying liquid is mixed with the mixed powder, an injectable slurry is formed. The mixed powder absorbs the solidifying liquid and solidifies to form an artificial bone.
7. The injectable artificial bone repair material according to claim 6, characterized in that: The main component or all components of the solidifying liquid are water.
8. The injectable artificial bone repair material according to claim 6, characterized in that: The liquid-to-solid ratio of the solidifying liquid volume to the mixed powder mass is 0.23:1 to 0.3:
1.
9. The injectable artificial bone repair material according to claim 6, characterized in that: The initial setting time of the injectable slurry is 2 to 9 minutes, and the final setting time of the injectable slurry is 4 to 13 minutes.
10. The injectable artificial bone repair material according to claim 6, characterized in that: One or more of a retarder, an active factor and an antibiotic may be added to the solidifying liquid.
11. A method for preparing an injectable artificial bone repair material according to any one of claims 1 to 10, characterized in that: The following steps are involved: S1: providing calcium sulfate powder; S2: obtaining calcium sulfate coarse powder by sieving calcium sulfate powder; S3: grinding the sieved calcium sulfate powder to obtain calcium sulfate fine powder; The particle size of the calcium sulfate coarse powder is 20 to 100 μm, and the particle size of the calcium sulfate fine powder is less than or equal to 7 μm; The coarse powder and the fine powder are mixed to obtain the mixed powder of the injectable artificial bone repair material.
12. A method for preparing an injectable artificial bone repair material according to claim 11, characterized in that: The preparation method of calcium sulfate is a normal pressure salt solution reaction method, an autoclave method or a hydrothermal reaction method.
